Effects of the specific characteristics of the CEO on accounting conservatism: a study in the US context. (2017) - Chouaibi, Jamel; Chiekh, Samira
Our research work investigated the effect of the specific characteristics of the chef executive officer (CEO) on accounting conservatism. Based on a sample of the 100 US firms for the year 2015, the main findings show that the manager's overconfidence has a negative and significant impact on the accounting conservatism of the companies. This shows that companies had better recruit over-confident executives since they would tend to present less conservative financial reports which would enhance the future profitability of the company. Similarly, the age of the leader has a negative and significant impact on accounting conservatism because younger leaders are more confident and more tolerant of risk than older ones. However, manager's experience has no effect on accounting conservatism.